Porous Metal Scaffolds for Hydrogen Storage - Ianni, Enrico (Curtin University, 2018)
Due to its thermodynamic, hydrogen specific weight, and volumetric properties, NaAlH4 is a promising candidate to store hydrogen for vehicular applications. However, NaAlH4 suffers from slow hydrogen absorption/desorption kinetics. A simple and cost-effective method for the synthesis of porous Mg and Ti-enriched porous Al scaffolds has been optimised. NaAlH4 was melt-infiltrated inside the porous Ti-enriched Al scaffold to investigate the combined effects of catalysis and nanoconfinement on its hydrogen desorption kinetics and thermodynamic properties.